ORGANIC RESIDUE AND PHOSPHORUS AS CONDITIONERS OF DEGRADED SOIL AND EFFECTS ON THE INITIAL GROWTH OF Dipteryx alata Vog. - Machado, Keila da Silva [UNESP]; Maltoni, Katia Luciene [UNESP]; Santos, Cinthia Montibeller; Rodrigues Cassiolato, Ana Maria [UNESP] (Centro Pesquisas Florestais, Ufsm, 2014)
In northwestern Sao Paulo State, it was established, in 1965, the hydroelectric station of Ilha Solteira (CESP) that produced extensive degraded areas, from where it was removed the soil superficial layers. For the re-establishment of the vegetation, in areas like these, it is necessary the addition of chemical inputs and organic material. Associating the presence in the area of macrophytes, to the need of recovery of degraded areas and the availability of seeds from native species of Cerrado, it was intended the development of this work, with the objective of evaluating the addition effects of organic residue and phosphorus on the material of degraded soil and on the initial growth of Dipteryx alata, arboreal species of 'cerrado'. The soil material was collected in area of degraded soil by the construction of Ilha Solteira hydroelectric station. The experiment was conducted in two environmental conditions, greenhouse and plenty of sun. The treatments consisted of four phosphorus doses (0, 100, 200 and 300 mg dm(-3) of P2O5), with or without macrophytes addition, with 16 treatments and 10 repetitions each one. The used macrophytes, collected at Jupia hydroelectric station, in Mato Grosso do Sul state, were dried, sliced, incorporated to the soil material and incubated during 60 days. The seeds of Dipteryx alata, collected around of the area, were sowed in washed sand and after 60 days introduced in the treatments. The plants were appraised monthly for height, stem diameter and leaves chlorophyll. After 210 days, the plants were collected and evaluated for fresh and dry weight of aerial part and radicular system and the soil material was evaluated for fertility and microbial activity by the carbon of liberated CO2. The organic residue, incorporated to the material of soil degraded, positively affects the soil fertility and the soil microbial activity. The applied phosphorus doses influenced the behavior of Ca, SB, H+Al and CTC, when applied in the absence of organic residue, it promoted significant and linear increments for values of potential acidity, and indicated the organic residue importance. The initial growth of the Dipteryx alata was favored by the protected cultivation, for the incorporation of organic residue and for the phosphorus addition to the soil. At the end although the material of degraded soil comes as good perspective for disposal of this residue, studies about the field conditions are necessary.
Keywords: vegetation re-establishment; macrophyte; soil fertility; soil microbiology